Análise técnico econômica da produção de hidrogênio verde através de energia eólica na cidade de Parnaíba-PI - Santos, Maria Eduarda Rebelo dos (Universidade Federal de São Carlos, 2025)
Green hydrogen, produced by electrolysis of water using renewable energy sources, stands out as a promising alternative for decarbonizing hard-to-abate sectors. Given the increasing global need to reduce greenhouse gas emissions, this energy carrier has been widely discussed as a crucial element in the energy transition and the achievement of international climate targets. In this context, Brazil emerges as a potential leader in green hydrogen production due to its predominantly renewable energy matrix, mainly composed of hydroelectric, wind, and solar sources, providing favorable conditions for large-scale electrolysis projects based on clean energy. In particular, the coast of Piauí offers an excellent wind profile, abundant freshwater resources, and strategic proximity to European ports. These geographical characteristics make the region highly suitable for both wind power generation and green hydrogen production. Therefore, the city of Parnaíba in Piauí was selected for this study, which evaluates the technical and economic aspects of electrolyzer technologies and wind generation within a remote self-production model. Metrics such as the levelized cost of hydrogen (LCOH) and net present value (NPV) were employed to assess the project’s economic viability. Additionally, a sensitivity analysis was conducted to evaluate the impact of various factors on production costs, complemented by a Monte Carlo simulation to incorporate uncertainties into the analyzed parameters. The model used PEM electrolyzers and wind turbines to simulate the production process, resulting in a cost of approximately R$ 8.53/kg (equivalent to USD 1.47/kg). This value is promising in the market, particularly in scenarios emphasizing decarbonization and energy transition.
Techno-economic analysis of green hydrogen production by wind power energy in the city of Parnaíba-PI
Keywords: Energia eólica; Hidrogênio verde; LCOH; NVP; Transição energética; Piauí; ENGENHARIAS::ENGENHARIA ELETRICA::SISTEMAS ELETRICOS DE POTENCIA